Female incontinence surgery: state of the art. Issue 1 (January 2015) - Marson, Francesco; Ammirati, Enrico; Gurioli, Alberto; Destefanis, Paolo; Gontero, Paolo; Frea, Bruno
Female urinary incontinence represents a medical and social problem with huge impact regarding both patent's quality of life and social costs. The diagnosis is important for therapeutic choice and should consider some factors: the degree of urethral mobility, urodynamics parameters, patent's will and expectations, information about surgical complications and risks. Nowadays suburethral sling evolution and bulking therapy for selected cases consent to perform miniinvasive surgery; the most relevant problem concerns the management of postoperative complications: in this sense autologous slings are used after urethrolisis. In most difficult cases, it is possible to consider artificial sphincter as the best option.